From Regional Security to Global IR : An Intellectual Journey. - Ayoob, Mohammed; Eun, Yong-Soo.; Acharya, Amitav; ProQuest (firma) (Boulder, CO : Lynne Rienner Publishers, 2024)
Mohammed Ayoob's work in the field of international relations, spanning more than four decades, offers invaluable insights into both international conflicts and the security dynamics of the Global South. From Regional Security to Global IR presents a chronological selection of that work from 1989 to 2024, providing a guide to Ayoob's intellectual journey and advancing the concept of Global IR as an inclusive approach to understanding the emerging decentralized world order.
The R2P Illusion -- The Strong Do What They Can -- Ch 15- From Regional Security to Subaltern Realism: My Intellectual Journey -- Beyond South Asia -- The Middle East -- Comparing Across Time and Space -- Centrality of the State -- International Norms -- Subaltern Realism: The Next Phase -- Moving On -- Notes -- References -- Contributors -- Index -- About the Book.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books